2009
DOI: 10.1016/j.febslet.2009.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Plant FtsZ1 and FtsZ2 expressed in a eukaryotic host: GTPase activity and self‐assembly

Abstract: a b s t r a c tPlants and algae contain the FtsZ1 and FtsZ2 protein families that perform specific, non-redundant functions in plastid division. In vitro studies of chloroplast division have been hampered by the lack of a suitable expression system. Here we report the expression and purification of FtsZ1-1 and FtsZ2-1 from Arabidopsis thaliana using a eukaryotic host. Specific GTPase activities were determined and found to be different for FtsZ1-1 vs. FtsZ2-1. The purified proteins readily assembled into previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 59 publications
3
24
2
Order By: Relevance
“…However, they reported that mixing FtsZ1 and FtsZ2 in equimolar reactions inhibited GTPase activity, whereas we observed a slight stimulation at 3 mM GTP and above. In assembly assays, Smith et al observed single protofilaments for individual and mixed FtsZ1 and FtsZ2, as reported for bacterial FtsZ (4,5), but indicated that the filament morphologies were unlike any observed for the bacterial proteins (23). In contrast, the morphologies of our assemblies appear more like those seen for bacterial FtsZs (e.g.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…However, they reported that mixing FtsZ1 and FtsZ2 in equimolar reactions inhibited GTPase activity, whereas we observed a slight stimulation at 3 mM GTP and above. In assembly assays, Smith et al observed single protofilaments for individual and mixed FtsZ1 and FtsZ2, as reported for bacterial FtsZ (4,5), but indicated that the filament morphologies were unlike any observed for the bacterial proteins (23). In contrast, the morphologies of our assemblies appear more like those seen for bacterial FtsZs (e.g.…”
Section: Discussioncontrasting
confidence: 52%
“…According to the primer sequences reported by Smith et al in their supplemental methods, their proteins were truncated after amino acids 39 and 73 for FtsZ1 and FtsZ2, respectively, which would have left a portion of the predicted transit peptide on FtsZ1 and removed conserved residues from the probable mature form of FtsZ2. Further experiments will be required to understand why our findings differ from those of Smith et al (23).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Biochemically, the plant FtsZ proteins behave in a similar fashion to bacterial FtsZ where both FtsZ1 and FtsZ2 are capable of binding and hydrolysing GTP, albeit at a lower rate compared with bacterial FtsZ (Smith et al 2010;Olson et al 2010). Recently, the enzymology of the plant FtsZs and how this relates to function has been under scrutiny.…”
Section: Biochemical Characteristics Of Plastid Division Componentsmentioning
confidence: 99%